Efetividade e segurança de talidomida e qualidade de vida relacionada à saúde em pacientes com mieloma múltiplo. - Paula Lana de Miranda Drummond (2022)
Multiple myeloma (MM) is an incurable cancer of plasma cells and affects mainly the elderly. The treatment of MM showed advances with the introduction of immunomodulators (eg thalidomide), proteasome inhibitors (eg bortezomib), and, more recently, new agents, contributing to an increase in life expectancy and health-related quality of life (HRQoL) of people with MM. However, the use of these drugs is also associated with adverse events (AE), some of them serious. The aim of the study was to evaluate the effectiveness and safety of therapeutic regimens containing thalidomide and its impact on the HRQoL of patients with MM. Patients undergoing MM treatment were recruited from two public health units and a private one in Belo Horizonte. The study had an observational design, divided into three components. In component 1 (retrospective cohort), the effectiveness and safety of treatment regimens for MM in patients (N=278) who started treatment between 2009 and 2020 were evaluated. Median times to death/progression were measured using the Kaplan Meier curves. The Cox proportional hazards model was used to measure the magnitude of the association (hazard ratio - HR) between death/progression and selected variables in univariate and multivariate analyses, and the incidence of AE according to treatment regimens was compared using the odds ratio (OR). In this component, the overall survival (OS) of patients was 99 months. In first-line treatment, the median time to progression-free survival (PFS) was 28 months. Polypharmacy patients who did not undergo transplantation had a higher risk of progression/death. The incidence of severe AE was low, but it was high for (39.6%) peripheral neuropathy. In component 2 (cross-sectional study), chemotherapy-induced peripheral neuropathy (CIPN) and its impacts on HRQoL and activities of daily living (ADL) of patients undergoing treatment were evaluated (N=217). The strength of association between CIPN and HRQoL and explanatory variables was estimated using the binary logistic regression method. Of the patients in this component, 90.3% had at least one CIPN symptom: 62.7% severe and 51.62% severely impacted ADL. CIPN was independently associated with education, hospitalization, treatment, adverse effects, disease symptoms, and global health status/HRQoL. In component 3 (prospective cohort), newly diagnosed patients (N=36) were followed from diagnosis to approximately 12 months of treatment. Median HRQoL scores before and after treatment were statistically compared, as well as the measure of HRQoL improvement/worsening and its association with selected variables. In this component, the summarized score, the functional and symptom scales, and the future perspective improved between diagnosis and the end of follow-up (p<0.05). Older patients, in polypharmacy, with severe CIPN and ISS III showed worsening of HRQoL (p<0.05). Generally, the study showed SG and SLP similar to other Latin American countries. Although HRQoL improves after firstline treatment, factors such as polypharmacy and AE can worsen it. The high occurrence of CIPN symptoms with an impact on ADL and HRQoL reinforced the need to monitor this AE and to prioritize the HRQoL of patients with MM.